2007
DOI: 10.1111/j.1365-2206.2006.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Child welfare workers who are exhausted yet satisfied with their jobs: how do they do it?

Abstract: A B S T R AC TIn response to a study of Canadian child welfare workers that unexpectedly found participants scoring high on a measure of emotional exhaustion (burnout) and, at the same time, high on overall job satisfaction, this paper reviews research that has investigated these constructs in the social work literature as well as in selected studies from sociology, social psychology, management and women's studies. The review reveals that some previous studies also report the coexistence of high levels of emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 41 publications
5
88
0
2
Order By: Relevance
“…This result was consistent with recent reflections by Radey and Figley (2007) and Stalker et al (2007), who similarly emphasized the importance of considering the positive effects of caring. Likewise, in the current study's analyses that controlled for both mindfulness and emotional separation, practitioners' higher personal distress scores (which reflect self-oriented distress in response to client distress) on the IRI were associated with lower levels of compassion satisfaction as compared with less distressed peers.…”
Section: Empathy and Emotional Separationsupporting
confidence: 82%
See 1 more Smart Citation
“…This result was consistent with recent reflections by Radey and Figley (2007) and Stalker et al (2007), who similarly emphasized the importance of considering the positive effects of caring. Likewise, in the current study's analyses that controlled for both mindfulness and emotional separation, practitioners' higher personal distress scores (which reflect self-oriented distress in response to client distress) on the IRI were associated with lower levels of compassion satisfaction as compared with less distressed peers.…”
Section: Empathy and Emotional Separationsupporting
confidence: 82%
“…Previous studies of compassion fatigue and burnout have provided important information about professional and workplace variables (e.g., caseload, supervision) that influence risk; as such, this information has significant policy implications for the helping professions that should be addressed (Badger et al, 2008;Bride, 2004;Sprang et al, 2007;Stalker, Mandell, Frensch, Harvey, & Wright, 2007). However, this awareness of risks associated with professional and workplace variables does not minimize the need to consider whether particular intrapersonal skills or abilities have potential to reduce risk of burnout and compassion fatigue, or to increase resilience and work satisfaction among helping professionals without jeopardizing empathic engagement and effective treatment relationships.…”
Section: Regression Analysesmentioning
confidence: 99%
“…Professionals working with survivors of child abuse are at high risk for adverse mental health outcomes (Walker, 2004). However, research also suggests the co-occurrence of emotional exhaustion and high job satisfaction (Stalker, Mandell, Frensch, Harvey, & Wright, 2007). Project 7 investigates the interplay of risk and protective factors for mental health outcomes among employees of a child protection service: the Danish Children Centres.…”
Section: Introductionmentioning
confidence: 99%
“…Resulting impacts include reduced performance, increased absenteeism, mistakes, psychological distress, job dissatisfaction, physical and mental ill health, and symptoms of burnout (cynicism, distancing from clients, depression and illness), which adversely affect client services (Dollard et al, 2001, p. 13;Schaufeli et al, 1993). Whilst primarily focused on distress, research has identified a proportion of CPW who, though affected by burnout, still experience job satisfaction (Stalker, Mandell, Frensch, Harvey, & Wright, 2007).…”
Section: Adversity Impacting Child Protection Workersmentioning
confidence: 99%
“…Research on resilience as it relates to CPW is very limited, particularly in the Australian context. Notwithstanding the adversity faced by CPW, many continue in this field, function effectively and report high job satisfaction (Conrad & Kellar-Guenther, 2006;Reagh, 1994;Stalker, Mandell, Frensch, Harvey, & Wright, 2007). Although strengths-based perspectives of resilience can inform research on CPW functioning and retention, the primary focus of research remains on deficit models and psychopathology.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%